The Doings of Philosophy of Education: An Interview with Claudia Ruitenberg - Ruitenberg, Claudia; Rocha, Samuel (Philosophical Inquiry in Education, 2024)
In this friendly conversation between colleagues, Claudia Ruitenberg talks with Sam Rocha about philosophy of education through the experience of being educated and doing the work of teaching, supervising, and writing philosophy of education. Biographical stories, reading habits, remarks on the reputation of the field, notes on method, and more emerge—and remain up for discussion.